Walking away from depression-motor activity increases ratings of mood and incentive drive in patients with major depression. (January 2017) - Bewernick, Bettina Heike; Urbach, Anne Sarah; Bröder, Arndt; Kayser, Sarah; Schlaepfer, Thomas Eduard
Abstract: Reduced motor activity is associated with depression. Lewinsohn's cognitive behavioural model of depression assumes a lack of positive experience due to a reduced level of activity as a key aspect of depression. The acute relationship between motor activity and mood as well as between motor activity and incentive drive (the motivation to engage in activities) is unknown. An augmentation of mood and incentive drive could precede or follow motor activity. We examined (1) whether motor activity would be correlated with the course of depression and (2) the temporal relationship between motor activity and acute changes in mood and incentive drive. Motor activity was measured with actigraphy in 12 patients with depression for one week. Severity of depression was assessed before and at the end of the study with depression rating scales. The patients reported mood and incentive drive once per hour. With lag sequential analysis, the temporal relationship between motor activity and mood and incentive drive was evaluated. Higher motor activity was associated with depression improvement. Motor activity had an acute association with mood and incentive drive, especially one hour after activity. The results support the Lewinsohn's model of depression and underline the impact of behavioural activation in antidepressant treatment. Highlights: The antidepressant effect of motor activity has been analysed. A higher level of motor activity was associated with an improvement in depression. A higher level of motor activity was associated with an acute augmentation of mood and incentive drive. The results support the Lewinsohn's model of depression. The impact of behavioural activation in antidepressant treatment was underlined.